Порівняльна характеристика понять юридичної та правозастосовної помилок - Прус, Ельвіра Уралівна; Прус, Эльвира Ураловна; Prus, Jel'vira (Одеса : Юрид. л-ра, 2012)
The article is devoted to the differentiation of the concepts of legal and law enforcement errors. Basing on the analysis of different scientific approaches, the author expresses her personal understanding of legal error features and formulates her own definition.
Прус Е. У. Порівняльна характеристика понять юридичної та правозастосовної помилок / Е. У. Прус // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 288-291.
Keywords: порівняльна характеристика; помилка; юридична помилка; правозастосовна помилка; сравнительная характеристика; ошибка; юридическая ошибка; правоприменительная ошибка; comparative characteristics; error; legal error; law enforcement error